E-LEARNING PADA PENDIDIKAN JARAK JAUH: KONSEP YANG MENGUBAH METODE PEMBELAJARAN DI PERGURUAN TINGGI DI INDONESIA - Darmayanti, Tri; Setiani, Made Yudhi; Oetojo, Boedhi (LPPM Universitas Terbuka, 2007)
For a long time, teaching and learning in a formal higher education is always means the meeting of teacher and learners in the classroom. The rapid changes in technology shift the paradigm of teaching and learning. The emerging in the use of the Internet changes the teaching and learning activities. Teaching and learning not only happends in the real classroom, but also in the virtual classroom where teacher and and learners separate physically. E-learning becomes a popular tool as an interactive tool for virtual education. However, the use and the implementation of e-learning in formal education are not as simple as it says. Since, changing paradigm of teaching and learning is a complicated process which involved many parties. The article discusses how e-learning changes the teaching and learning in a formal higher education in Indonesia. The article also discuss the prior experience of Universitas Terbuka, as a distance education institution in Indonesia, in implementing the teaching and learning through the Internet